Little Burgundy Narratives: a case study of church repurposing, technology, arts, and civic commons - Eleonora Diamanti; Kaj Huddart; Michael Jemtrud (In_Bo, 2017)
This paper focuses on the specific case study of the Church of St. Joseph, a parish church situated in the neighborhood of Little Burgundy in the South-West borough of Montreal. It addresses first the historical arc that has led to the church’s repurposing before discussing the specific intervention of Little Burgundy Narratives, a digital portrait of the neighborhood surrounding the former Church of St. Joseph in an effort to support its new role as a community space, harnessing technology and the arts to enhance the church’s value as a civic common. The former Church St. Joseph is a witness of the growing disuse and re-purpose of places of worship and is a relevant case-study for the understanding of the future of churches in urban areas.